Ambienti sensoriali "terapeutici" che rendano Abili Un progetto integrato di vita per persone con Disturbi dello Spettro Autistico - bellini, elena (Premio Tesi di Dottorato, 2019)
People with Specific Learning Disabilities (SLD) have a particular sensory sensitivity, causing their surrounding environment to affect the quality of life significantly. It is called a "spectrum", because there is a great variety of behaviours making it difficult to define universal and design criteria. These behaviours do however require a new dynamic and flexible approach, enabling the customization of the feedback to the project. Starting from the study of the specific needs of users, the environmental conditions and the design approaches, this research aims at providing innovative tools to support the design of "therapeutic" environments which could reduce the discomfort and stress related to the person's enablement, in order to include them in the social community within an integrated life project, concerning "home", applied living spaces (school, work, day centres...) and emergency conditions with respect to treatments.